Effects of Vanadium on the growth, chlorophyll, and mineral content of Soybean (Glycine max (L.) Merr) - Sozudogru Ok, Sonay; Cihat Kutuk, A.; Halilova, Hanim (Ciencia, 1970)
The effect of increasing levels of vanadium (0, 0.5, 1, and 2 mg Vkg-1) and farmyard manure (FYM) (O, 1 and 2 ton ha-1) on the fresh and dry weight, chlorophyll and mineral content of soybean (Glycine Merr (L.) Merr) was investigated under the greenhouse conditions. Phenologic observations showed that V concentrations were not toxic to the growing plants. Fresh and dry weights of the plants were decreased by applying V or FYM doses while both V and FYM treatments increased the plant growth. Nodule number was only affected by applications of 1 mg kg-1 V and 1 ton ha-1 FYM doses. Increasing V concentrations caused increases in chlorophyll contents and fresh and dry weights of plants. On the other hand both V and FYM treatments had similar effects on soybean.